Peningkatan Kompetensi Guru dalam Pembentukan Karakter Spiritual Santri melalui Pengajian Kitab Kuning di Ponpes Putra Al-Ishlahuddiny Kediri Lombok Barat - Karmani, M. Ali (TSAQOFAH, 2021)
To be person with character, means become best person. Hence, grwoing up with character means develop with our ethic and intelectual potential. The maturity of people includes on capacity of loving and working. Then virtue as emphaty, affection, sacriface, loyaty, and forgiveness are our power to love while virtue as initiative effort, persistence of discipline, and diligence are our ability to work and become competent person on our tasks of life.To understand this way, work ethic and competency are not seperated from our character, however those things are part of us. Even, how good we do working, how is our accuracy and words to do a small or big work as one of mportant way to influence other people quality of life. Therefore, it is needed hard work to develop our talent so we can utilize to produce postitive different in the world. The method in this thesis used qualitative approach and data collection used obeservation, interview, and documentation.Pondok Pesantren Putra Al-IshlahuddinyKediri insists character values for santri through several ways and methods, like educating without dressing them down, giving them example, accustoming santri with al qur’an interaction, memorizing, dzikir, pray, habituating santri to behave well for everyday, both at home and in cottage. This program will be runned well because santri stays in dormitory of pesantren.